2008
DOI: 10.1039/b801561a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Al complexes containing phenoxy-imine ligands and their use as the catalyst precursors for efficient living ring-opening polymerisation of ε-caprolactone

Abstract: Al complexes containing phenoxy-imine ligands of type, Me2Al[O-2-R1-6-(R2N=CH)C6H3] [R1 = Me, R2 = 2,6-iPr2C6H3 (1a), tBu (1b); R1 = tBu, R2 = 2,6-iPr2C6H3 (2a), tBu (2b), cyclohexyl (2c), adamantyl (2d), C6H5 (2e), 2,6-Me2C6H3 (2f), C6F5 (2g)] have been prepared in high yields from AlMe3 by treating with 1.0 equiv. of 2-R1-6-(R2N=CH)C6H3OH in n-hexane. Structures for 1a, 1b, 2a-e and 2g were determined by X-ray crystallography, and these complexes have a distorted tetrahedral geometry around Al; both the Al-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…The catalytic activity in the ring-opening polymerization (ROP) of ε-caprolactone initiated by 2, 3, 6, or 7 in combination with n BuOH increased in the order: 3 > 2 > 6 > 7, indicating that the imino substituent (R) plays an important role for the efficient ROP [43]. The role of the imino substituents for efficient and controlled ROP was further remarked in an extension of this study, showing that in the presence of C6F5 as imino substituent, the ROP of ε-caprolactone took place in a living manner [40]. Notably, the ROP reactions were accompanied by a certain degree of transesterification as side reaction except for the polymerization carried out in the presence of complexes bearing the C6F5 substituent.…”
Section: Salicylaldiinato-aluminum Complexes In the Ring-opening Polymentioning
confidence: 75%
“…The catalytic activity in the ring-opening polymerization (ROP) of ε-caprolactone initiated by 2, 3, 6, or 7 in combination with n BuOH increased in the order: 3 > 2 > 6 > 7, indicating that the imino substituent (R) plays an important role for the efficient ROP [43]. The role of the imino substituents for efficient and controlled ROP was further remarked in an extension of this study, showing that in the presence of C6F5 as imino substituent, the ROP of ε-caprolactone took place in a living manner [40]. Notably, the ROP reactions were accompanied by a certain degree of transesterification as side reaction except for the polymerization carried out in the presence of complexes bearing the C6F5 substituent.…”
Section: Salicylaldiinato-aluminum Complexes In the Ring-opening Polymentioning
confidence: 75%
“…For ligands containing both oxygen and nitrogen as potential bridging atoms, it is found that compounds having oxygen bridges between aluminium atoms [23,24,39,[47][48][49][50] predominate over those with nitrogen bridges. [37,51] Examples are known with both O and N atoms bridging in hydroxypyridine ligands (in an isolobal disposition to carboxylatebridged ligands) [25] or with an amidate group [52][53][54][55] between two aluminium atoms.…”
Section: Resultsmentioning
confidence: 98%
“…Bidentate N,O-donor ligands [20][21][22][23][24][25] constitute simple nonsymmetric chelating structures that impose control over the metal coordination geometry with a sterically demanding chelating structure. Phenoxidoimido [26][27][28] and the closely related phenoxido-amino bidentate systems [29][30][31] have been widely used for transition metals and to produce alkylaluminium complexes and their cationic derivatives, [32][33][34] which can be utilized as catalysts in ROP processes [24] of heterocyclic monomers and in ethylene polymerization reactions. [21,35] Here we report the synthesis and structural analysis of the reaction products from the treatment of iminophenol and aminophenol ligand precursors with alane AlH 3 ·NEtMe 2 to prepare derivatives of different nuclearity.…”
Section: Introductionmentioning
confidence: 99%
“…[98][99][100][101][102][103][104][105][106][107] Nomura [98] studied the aluminum complexes containing phenoxyimine ligand for initiating polymerization of ɛ-caprolactone and found that the aluminum complexes 71 exhibited living polymerization characteristics when low monomer conversion, increasing conversion resulted in widening the PDI of PCL. Redshaw [99] also investigated the aluminum complexes 72 and 73 for ROP of ɛ-caprolactone, these catalyst system showed produced polymers with 44640 g/mol molecular weight, but, 46% monomer conversion.…”
Section: No Ligandmentioning
confidence: 99%